2012
DOI: 10.1039/c2cc35283d
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid-catalyzed Friedel–Crafts alkylations of 3-hydroxy-2-oxindole: an efficient approach to the core structure of azonazine

Abstract: A Lewis acid catalyzed Friedel-Crafts reaction of electron rich aromatics with 3-alkyl-3-hydroxy-2-oxindole (5) has been developed. The methodology provides a straightforward access to the core of azonazine (2) sharing an all-carbon quaternary stereocenter at the tetracyclic ring junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Bisai et al 39 To access enantioenriched benzofuro [2,3-b]indoles, N-mesyl-protected proline was employed as a chiral auxiliary and attached to the nitrogen atom of skatole (Scheme 39). The hydroarylation of 138 with p-cresol (127) afforded indolines 139a and 139b as a 2.8:1 mixture of C3-epimers.…”
Section: Scheme 36mentioning
confidence: 99%
“…Bisai et al 39 To access enantioenriched benzofuro [2,3-b]indoles, N-mesyl-protected proline was employed as a chiral auxiliary and attached to the nitrogen atom of skatole (Scheme 39). The hydroarylation of 138 with p-cresol (127) afforded indolines 139a and 139b as a 2.8:1 mixture of C3-epimers.…”
Section: Scheme 36mentioning
confidence: 99%
“…3 Owing to their wide occurrence in natural products, drugs and value-added products, 3,3-disubstituted 2-oxindoles 4 are important class of compounds those have been used as advanced intermediates. 7 Later, we have also reported an efficient reactions of 3-hydroxy-2oxindoles with a variety of 2- substrates such as allyl/methallyl trimethylsilane, phenylacetylene, acetophenone, styrene, and electron-rich aromatics. 6 Towards this, we have recently developed Lewis-acid catalyzed efficient F-C alkylations of electron-rich aromatics with a variety of 3-hydroxy 2-oxindoles and its application in tetracyclic core of Azonazine (1a) (Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…It was observed that elevated temperature afforded products in 72-81% isolated yields only in 2 h, whereas at room temperature the reaction became sluggish (entries [1][2][3][4]. [7][8]14 Interestingly, it was found that 10 mol% of metal triflates such as Cu(OTf) 2 , Sn(OTf) 2 , In(OTf) 3 , and Bi(OTf) 3 were found to be good catalysts for efficient F-C alkylations, which resulted products (±)-8a in 87%, 89%, 92%, and 90%, respectively in 2h (entries 5-7 and 12). [7][8]14 Interestingly, it was found that 10 mol% of metal triflates such as Cu(OTf) 2 , Sn(OTf) 2 , In(OTf) 3 , and Bi(OTf) 3 were found to be good catalysts for efficient F-C alkylations, which resulted products (±)-8a in 87%, 89%, 92%, and 90%, respectively in 2h (entries 5-7 and 12).…”
Section: Introductionmentioning
confidence: 99%
“…6 Similarly, Friedel-Crafts-type reactions have recently been done with 3-hydroxy-2-oxyindoles to provide aryl-substituted 2-oxyindoles. 7 Nevertheless, new synthetic routes to aryl-substituted 2-oxyindoles are highly sought after, especially those producing novel structures. In the following letter, we describe a synthetic methodology leading to highly functionalized 2-oxyindoles.…”
Section: Introductionmentioning
confidence: 99%